Pains and Suffering - When Compassion and Consolation get Serious - Wils, Jean-Pierre (Concilium, 2025)
Human beings are creatures that need comforting. In a culture in which getting on, getting things done and ambition for a successful life signpost the way ahead, those who stumble and fall and those who "can no longer keep up" are ultimately unwelcome guests, who remind us of our fundamental finiteness. But awkward things do happen in our lives. Not all bad events can be put right. Not every plan that had steered our path into a bright future but came to a standstill can be put back on to the right path. People are confronted with the irreparable, which cannot be treated, and certainly not reversed. The situation becomes serious as soon as pain and constant suffering bring clouds and even darkness over our lives. Help reaches a limit; a return to our previous state is no longer possible. A corner has been turned, and we cannot go back to our old lives. Now is the time for consolation. But what is consolation? And why is pain, physical and mental pain, something like the nucleus of the need for consolation? What happens to us when we become creatures with pain? Can anything save us from the hopelessness of suffering? What is the meaning of giving consolation in this situation, and how can it succeed? How far do our attempts at consolation get?